Performance evaluation of IOT systems – basic issues - V. Sowmya, K; JKR Sastry, Dr (International Journal of Engineering and Technology, 2018)
Internet of things (IOT) is a layered network and generally heterogeneous as communication between small things like digital cameras and big things like servers has to happen. The communication speeds of various devices connected on to IOT are in great variance affecting the performance of the entire network. The small devices connected on to IOT are fragile in the sense that they tend to fail quite often affecting the performance of the network. The small devices are low in energy depletion of which is rather fast. The small devices also have heavy latency. Many such issues exists that effect the performance of an IOT network. In this paper, various issues/bottlenecks that hamper the performance of an IOT network are and a mitigation strategy for improving the performance of the IOT networks is discussed.